Exploring Legitimation Code Theory and TikTok: Knowledge Codes and Semantic Profiles in Finfluencer Discourse - Bannister, Peter; Santamaría Urbieta, Alexandra; Alcalde Peñalver, Elena (Revista Alicantina de Estudios Ingleses, 2026)
This exploratory study employs Legitimation Code Theory (LCT), a theoretical framework for analysing knowledge practices across disciplinary and social contexts, to elucidate the construction and legitimisation of financial knowledge on TikTok, a platform witnessing a surge in informal financial literacy education. A meticulously curated multimodal corpus of financial influencer (‘finfluencer’) videos (n=100; 50 English, 50 Spanish) underwent rigorous analysis utilising key LCT constructs. Specifically, we examined semantic gravity (the degree to which meaning relates to specific contextual referents) and semantic density (the concentration of meaning within symbols or practices) to generate nuanced semantic profiles that illuminate knowledge-building practices. Empirical semantic profile mapping revealed a striking dichotomy: English-language videos predominantly exhibited prosaic codes, characterised by high interconnectivity between financial concepts and everyday applications, facilitating accessibility whilst maintaining conceptual coherence. Conversely, Spanish-language videos manifested primarily rarefied codes, distinguished by abstract financial terminology with limited contextual grounding and reduced practical interconnections. This linguistic divergence intimates that cultural and linguistic milieus profoundly shape the contours of financial knowledge dissemination across digital platforms. Further comparative analysis revealed a significant correlation between finfluencer popularity metrics and discourse characteristics; those with larger followings tended towards weaker semantic gravity and greater abstraction, corroborating theoretical postulations that elevated platform status bolsters claims to knowledge legitimacy. The findings underscore LCT’s efficacy in illuminating the intricate interplay among cultural contexts, platform-specific power hierarchies, and symbolic capital in the online propagation of financial concepts. This research offers valuable insights into the multifaceted dynamics of knowledge legitimisation in digital spaces, potentially informing future strategies for developing cross-cultural financial literacy programmes that acknowledge diverse knowledge-building practices.
Keywords: legitimation code theory; discourse analysis; TikTok; financial literacy development; cross-cultural communication